An Analysis of Speech Act in Harry Potter: The Prisoners of Azkaban - Nopriansah Nopriansah; Silvia Sembiring; Yohana Restu Wilis; Nurul Septi Adianti Awal (Literary Criticism, 2020)
In speaking activities, speakers not only communicate messages, but also develop social relationships with other speakers (speech companions). Based on Hymes' theory, this study focuses on the function of context in conversational discourse between close characters in the Harry Potter: The prisoners of Azkaban. The purpose of this study is to determine the role of context in conversational discourse between characters, as well as to analyses conversations between close characters based on hymes theory; from these conversations, it can be seen that paralinguistic elements are very helpful for understanding each other's illocutionary. Utilizing a qualitative descriptive method with a content analysis approach, the research method is qualitative. Keyword: Follow Conversation, Abstract Context, Harry Potter